(untitled) (Journal of Environmental Bioremediation and Toxicology, 2023)
The Northern Guinea Savannah ecological zone of Nigeria, with its rich history of pepper production, faces challenges like diseases, pests, and weed management issues, resulting in lower yields compared to Western Europe. This investigation explores the prevalence and virulence of fungal pathogens affecting pepper cultivation in this region, specifically in Jalingo and Yola, characterized by distinct wet and dry seasons. The study employed a complete randomized design for laboratory investigations and split plots for screenhouse pathogenicity tests, taking into account different pepper cultivars. It identified five primary fungal pathogens responsible for fungal diseases: Fusarium oxysporum, Colletotrichum capsici, Fusarium solani, Phoma species, and Aspergillus niger. Fusarium oxysporum was the most frequently isolated fungus, comprising 91.7% of occurrences, particularly notable during seedling and maturity stages. Colletotrichum capsici, Fusarium solani, Phoma spp., and Aspergillus niger followed in frequency. These pathogens exhibit varying levels of virulence on pepper tissues, with fruits being more susceptible than leaves. Fusarium solani, notably, induces severe rot on Capsicum annuum fruits, with a pathogenicity level of 68.8%. This research offers valuable insights into the prevalence, virulence, and diversity of fungal pathogens affecting pepper crops in the Northern Guinea Savannah. The suggested recommendations for integrated disease management and cultivar improvement provide essential guidance for promoting sustainable pepper production in the zone.